The ebb and flow of Chinese petroleum : a story told by a witness - Huahe, Mao (Ideas, history, and modern China, 2019)
"For the first time, a work that breaks with the official Chinese government narrative concerning the petroleum industry and provides the true story as personally experienced by the author, Mao Huahe, a thirty-year veteran and executive in the oil industry. Mao witnessed first-hand the breakthrough discovery of the Daqing Oilfield, the behind-the-scenes political machinations and turmoil of the Cultural Revolution and the subsequent reform and opening period, and details the effects these events had upon China's petroleum industry"--